(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The homestay tourism model has emerged as a transformative force in rural destinations, especially in ecologically rich and culturally vibrant regions such as Garhwal in Uttarakhand, India. This review paper synthesizes findings from existing research, particularly